Innovations for Successful Electronic Medical Records (EMR) Implementation in Hospitals: Inovasi untuk Keberhasilan Implementasi Rekam Medis Elektronik (EMR) di Rumah Sakit - Sandhe, Dhiyan Sandhe Kurniawan; Krisnana, Ilya; Pradanie, Retnayu (Indonesian Journal of Innovation Studies, 2025)
General Background: Electronic Medical Records (EMR) enhance healthcare efficiency, cost-effectiveness, and data accessibility. However, implementation remains uneven globally. Specific Background: Despite Indonesia’s Ministry of Health Regulation No. 24 of 2022 mandating EMR adoption, many hospitals struggle with infrastructure, workforce limitations, and regulatory challenges. Knowledge Gap: While studies highlight EMR benefits, limited research addresses specific barriers in Indonesian hospitals and effective implementation strategies. Aims: This study identifies EMR adoption challenges and explores strategies for successful implementation in Indonesia. Results: Key barriers include inadequate infrastructure, unclear policies, insufficient training, and connectivity issues. Pre-implementation planning and structured training improve outcomes. Novelty: This study systematically analyzes Indonesia-specific EMR challenges and presents actionable solutions. Implications: Hospitals require better preparation, clear policies, and government support to ensure seamless EMR integration, fostering healthcare digitalization. Highlights: Regulatory Compliance: Despite mandates, many Indonesian hospitals struggle with full EMR adoption due to infrastructure and policy gaps. Key Barriers: Limited resources, lack of training, and unstable internet hinder effective EMR implementation. Strategic Solutions: Pre-implementation planning, technical support, and structured training improve adoption success. Keywords: Barriers, Strategy, Electronic Medical Record, Hospital